Communication Methods Used by the Bumela Youth Organization to Accelerate the Development of Youth Potential in Rural Areas - Suryani, Wahidah; Dako, Restiarani Saputri; Hidayatullah, Hidayatullah (Proceeding International Conference on Religion, Science and Education, 2026)
This article investigates how organizational communication practices shape the development of youth self-potential in Karang Taruna Mandiri, a village-level youth organization in Bumela, Gorontalo Regency, Indonesia. The study aims to identify the main organizational communication methods used and the barriers that hinder their effectiveness in supporting youth empowerment. Adopting a qualitative descriptive case study, data were collected through passive participant observation, semi-structured interviews with ten current and former leaders and members, and analysis of organizational and regulatory documents. Data were reduced, displayed, and interpreted through iterative thematic analysis. The findings indicate that four communication methods—informative, persuasive, directive or coercive, and human-relations–oriented—are present but only partially institutionalized. Informative communication is uneven and largely confined to WhatsApp messages, persuasive efforts are sporadic and tied to specific events, directive strategies range from past coercive pressure to current non-directive leniency, and human-relations communication emphasizes understanding members’ busyness but normalizes non-participation. These patterns, summarized in two tables, are compounded by structural barriers (unclear programs, lack of routine activities, weak coordination with village government, suboptimal use of media) and human-relations barriers (time conflicts, low conflict-resolution skills, limited literacy application, and minimal recognition). Together, they generate both overt and silent resistance, reflected in low attendance, irregular contributions, and muted feedback. The study contributes to organizational communication and resistance research by illustrating how silence, semantic narratives, and interaction structures interact in a rural youth organization. The results underscore the importance of establishing clearer communication routines, more dialogic leadership, and simple participation monitoring to foster youth self-potential and inform future interventions and mixed-methods research.